Additions to the holothuroid fauna of the southern African temperate faunistic provinces, with descriptions of new species - Thandar, Ahmed S. (Zootaxa, 2008)
This paper is the third and the final one in the series reporting on the numerous lots of unidentified holothuroids received from the South African and Natal Museums. While the first two papers were limited to the fauna of the subtropical east coast, this paper is limited to the fauna of the temperate region of southern Africa, west of the Port St. Johns-East London area, encompassing the warm and cold temperate faunistic provinces, stretching into Namibia. It records and/or describes 23 nominal and four indeterminate species of mostly dendrochirotid holothuroids. Altogether seven new species and three new records for the region under consideration are included and some new data presented for previously described but poorly known species, where this was lacking. The new species are Sclerothyone unicolumnus, Ocnus rowei, Cladodactyla brunspicula, Panningia trispicula, Psolidium pulcherrimum, P. pseudopulcherrimum and Synallactes samyni whereas the new records for South Africa are Pannychia moseleyi Théel; for the temperate region, Pawsonellus africanus Thandar; and for Namibia, Pseudoaslia tetracentriophora Heding.